Margen de apreciación nacional, diálogo judicial y argumentación racional: notas desde la experiencia peruana - Grández Castro, Pedro P. (2021)
The paper analyzes the presence of the national margin of appreciation doctrine (NMA) in the reasoning developed in the inter-American human rights system, from a perspective of articulation between the Inter-American Court jurisdiction and States internal jurisdictions. The argument that is defended in the paper maintains that, in the framework of an open process of implementation of a globalized model of constitutionalism, a certain level of NMA is not only necessary for the inter-American judicial dialogue, but also even indispensable. In order to achieve this objective, the work has three parts: the first presents a brief summary of the NMA doctrine and its justification; the second presents the debate developed in this regard in the inter-American system; and the last one shows an example of a rational interaction model based on the Peruvian case of conventional control of the amnesty received by President Alberto Fujimori.